(3SDGd hLhGH aj Mb Gdjbjf hYjf Gdjbjf hYde Gdjbjfs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3eSFdI ai bhdg JYGdi Mb Gdjbjf hYjf Gdjbjf hYde Gdjbjf aeG eYfi cd ebGe efgG hCi ebGe CYdi GdLhGH GdMeO ddg QH GdYGdejf ddfGS ai gPg GdCSeGA ebGdGJ eYQhaI efgG Cf jbGd s
(3BNQgG (B:s
(3GdJi gi MbjbI EjGc fSJYjf cGf gPG ahb eG jLOg cd CMO de jLO eKd gPG hGddg CYde JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
Keywords: (3Gdabg GdMfHdjs